Evaluation of dihydropyranocoumarins as potent inhibitors against triple-negative breast cancer: An integrated of in silico, quantum & molecular modeling approaches - Abu Yousuf Hossin; Md Naziur Rahman; Md Mahabub Hasan; Ansarul Karim; Shyikh Ahmed Alif; Naziat Nayel Arshi; Shammi Jahan; Ajoy Kumer (PLoS ONE, 2025)
Triple-negative breast cancer (TNBC) characterizes one of the most antagonistic subtypes of breast hostilities, due to lacking targeted and potential therapies. In this study, it is investigated and performed an integrative in silico investigation into the pharmacological potential of a series of dihydropyranocoumarins (Visnadine (L01), Pteryxin (L02), Isosamidin (L03), and Suksdorfin (L04)) as forthcoming TNBC therapeutics. A many-sided computational workflow was employed encompassing quantum chemical calculations, drug-likeness profiling, in silico, molecular docking, and molecular dynamics (MD) simulations. First of all, all ligands were sourced from the PubChem database and performed the geometry optimization with calculating the quantum descriptors using Density Functional Theory (DFT) via the DMol³ module in BIOVIA Materials Studio, applying the B3LYP functional and DNP basis set. Frontier molecular orbital (FMO) analyses in terms of HOMO–LUMO energy gaps and associated global reactivity descriptors, were evaluated to ascertain electronic stability and reactivity trends. Subsequent, PASS prediction, drug-likeness and ADMET assessments, performed using way2drug, SwissADME and pkCSM platforms, revealed favorable pharmacokinetic profiles, with all candidates exhibiting high gastrointestinal absorption, acceptable aqueous solubility, and minimal cytochrome P450 inhibition. Next, Target-based molecular docking against key TNBC-related proteins (PDB IDs: 5HA9 and 7L1X) was conducted using AutoDock Vina within PyRx. These complexes were further validated through 100-ns all-atom MD simulations using Desmond software under the AMBER14 force field, demonstrating stable RMSD values and compact, persistent protein–ligand interactions throughout the simulation period. For resulting, to begin with, PASS prediction suggested high probabilities for antineoplastic activity, substantiating their biological relevance, and initially, it was revealed that the ligands showed the anti-cancer properties. Next, despite predicted hepatotoxicity, the compounds showed no AMES mutagenicity or genotoxicity, indicating an acceptable safety profile. Overall, dihydropyranocoumarins, especially L03, emerge as promising TNBC leads. Docking analysis revealed strong binding affinities across the ligand set, with Isosamidin (L03) showing the most pronounced interaction (−9.1 kcal/mol), primarily mediated through hydrogen bonding and π-stacking interactions within the active sites. On based on quantum calculation, among the derivatives, L01 exhibited the highest chemical stability, while L04 showed greater electrophilic reactivity, as reflected in the MEP surface and charge distribution profiles. Lastly, the MD indicates indicative of strong conformational stability under physiological conditions of docked complex by RMSD, RMSF, SASA, H bonding and interactions. However, these in silico studies and computational approaches warrant to the future scope for experimental validation through in-vitro assays such as MTT cytotoxicity, apoptosis induction, and cell migration studies to confirm the anti-TNBC potential of these compounds.